With or Without the Self? Arguments in Favor of the Hindu Concept of the Atman over the Buddhist Understanding of the Anatman - Astore, Rocco Angelo (Conatus - Journal of Philosophy, 2021)
As found in the Upanishads, readers come to encounter many ideas regarding the “Self” as opposed to the “self,” or the Atman versus the atman. Now, complicating matters further readers encounter the antithetical concept, of the Atman and atman, or the Buddhists understanding of the anatman as found in the Dhammapada. First, this piece will unpack the idea of both the “Self” and the “self,” or the Atman and the atman, as understood in Hindu philosophy and theology. Next, this essay will then describe the Buddhists understanding of anatman, or the absence, or emptiness of the self, or the nullification of the self, or the atman as well as even of the Self, or the Atman. Finally, this piece will resolve by arguing in favor of the Self, or the Atman as well as the self, or atman over the Buddha’s notion of the anatman.